Dynamics of critical fluctuations: theory - phenomenology - heavy-ion collisions - Bluhm, Marcus; Kalweit, Alexander; Nahrgang, Marlene; Arslandok, Mesut; Braun-Munzinger, Peter; Flörchinger, Stefan; Fraga, Eduardo S.; Gazdzicki, Marek; Hartnack, Christoph; Herold, Christoph; Holzmann, Romain; Karpenko, Iurii; et al. (Nuclear physics. A, Nuclear and hadronic physics, 2020)
This report summarizes the presentations and discussions during the Rapid Reaction Task Force “Dynamics of critical fluctuations: Theory - phenomenology - heavy-ion collisions”, which was organized by the ExtreMe Matter Institute EMMI and held at GSI, Darmstadt, Germany in April 2019. We address the current understanding of the dynamics of critical fluctuations in QCD and their measurement in heavy-ion collision experiments. In addition, we outline what might be learned from studying correlations in other physical systems, such as cold atomic gases.
Gesehen am 18.01.2021